Weyl fermions in antiferromagnetic Mn3Sn and Mn3Ge - Kuebler, J.; Felser, Claudia (EPL - Europhysics Letters, 2017)
The anomalous Hall effect in the noncollinear antiferromagnetic metals Mn3Ge and Mn3Sn has been observed after a theoretical prediction made by us (Kübler J. and Felser C., EPL, 108 (2014) 67001). The experimental values of the anomalous Hall conductivities (AHC) are large as are the theoretical values. Recently measured thermoelectric properties mirror the large AHC and clearly show that the transport is by quasiparticles at the Fermi energy. We here make an attempt to unravel the origin of the large AHC and show that both Mn3Sn and Mn3Ge host Weyl points, which were recently discovered in semimetals. For this purpose we determine the electronic structure ab initio in the local spin-density functional approximation. The Weyl points are found to occur below the Fermi energy and we argue that spots of large Berry flux ("hot spots") that are seen at the Fermi surface are produced by the Weyl nodes.
CRIS-Team Scopus Importer:2022-04-14